THE ROLE OF FAMILY COMMUNICATION IN DEVELOPING EARLY CHILDHOOD'S INTEREST IN READING - Musawir, La Ode Abdul; Sudu, La; Latif, Abdul; Amos, Amos; Yusnita, Yusnita; Keke, Ahmat (Noble Cendekia Indonesia, 2024)
This article is entitled The Role of Family Communication in Developing Early Childhood Reading Interests. This article looks at family communication which is very important in making children have a high interest in reading where both parents are the first school for children, especially early childhood. The method used is a literature study by taking references related to the role of family communication and the development of children's reading interests at an early age. The results of the study showed that fostering reading interest in early childhood is done by parents not only by giving orders to children but by providing the best example, namely parents showing great love for books, then the most important thing is to provide assistance when children read and answer correctly related to questions asked by children with language that is understood by children